Anomalous variation of the mechanical behaviour of ferroelastic La0.6Sr0.4Co0.2Fe0.8O3-δ during the ferro-to-paramagnetic transition. (1st April 2015) - Araki, Wakako; Abe, Takehiro; Arai, Yoshio
Abstract : Uniaxial compression tests of ferroelastic La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ were conducted in the temperature range covering the ferro-to-paramagnetic transition at ∼240 K ( T c ). An anomalous variation of mechanical behaviour was observed. The apparent elastic modulus drastically decreases above T c, whilst it is almost constant below T c ; on the other hand, the critical stress for ferroelastic domain switching decreases monotonically with increasing temperature. Furthermore, the back-switching occurs easily and/or rapidly below T c, but the material becomes brittle.